199k views
1 vote
Solve for w.

14 + 3(–w + 6) = –11w

w =

2 Answers

3 votes

Answer:

w= -4

work:

14-3w+18=-11w

32-3w=-11

-3w+11w=-32

8w=-32 divide by 8 then you will get your answer

w=-4

User Spencer Goff
by
5.7k points
2 votes

Answer:

w = -4

Explanation:

→Distribute the 3 to (-w + 6):

14 + 3(-w + 6) = -11w

14 -3w + 18 = -11w

→Add like terms:

-3w + 32 = -11w

→Add 11w to both sides:

8w + 32 = 0

→Subtract 32 from both sides:

8w = -32

→Divide both sides by 8

w = -4

User Avez Raj
by
5.7k points